2023
DOI: 10.1002/cam4.6173
|View full text |Cite
|
Sign up to set email alerts
|

The role of DYNLT3 in breast cancer proliferation, migration, and invasion via epithelial‐to‐mesenchymal transition

Abstract: PurposeDYNLT3 is identified as an age‐related gene. Nevertheless, the specific mechanism of its carcinogenesis in breast tumor has not been clarified. This research aims to elucidate the role and the underlying molecular pathways of DYNLT3 on breast cancer tumorigenesis.MethodsThe differential expression of DYNLT3 among breast cancer, breast fibroids, and normal tissues, as well as in various breast cancer cell lines were detected by immunohistochemical staining, real‐time quantitative reverse transcription‐PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
(89 reference statements)
0
2
0
Order By: Relevance
“…It is known that specific breast cancer 1/2 (BRCA1/2) mutations in the worldwide population are highly ethnic-specific [30], with a high frequency of BRCA variation in specific countries or ethnic groups, especially within genetically isolated populations, where these mutations are descendent from a single founder [41]. Wang (2023) summarized the main factors that contribute to the ethnic specificity of the BRCA variation, such as strong positive selection on human BRCA, adaptation to the living environment, genetic drift and founder variation in different ethnic populations [30]. BRCA1 and BRCA2 mutations are estimated to be responsible for about 3% of all BCs and other less common high-penetrance genes account for less than 1% of all BCs [42].…”
Section: Genetics/genomics Of Breast Cancer Disparitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that specific breast cancer 1/2 (BRCA1/2) mutations in the worldwide population are highly ethnic-specific [30], with a high frequency of BRCA variation in specific countries or ethnic groups, especially within genetically isolated populations, where these mutations are descendent from a single founder [41]. Wang (2023) summarized the main factors that contribute to the ethnic specificity of the BRCA variation, such as strong positive selection on human BRCA, adaptation to the living environment, genetic drift and founder variation in different ethnic populations [30]. BRCA1 and BRCA2 mutations are estimated to be responsible for about 3% of all BCs and other less common high-penetrance genes account for less than 1% of all BCs [42].…”
Section: Genetics/genomics Of Breast Cancer Disparitiesmentioning
confidence: 99%
“…Among these deregulated genes, dynein light chain Tctex-type 3 (DYNLT3), prolyl 4-hydroxylase subunit alpha 3 (P4HA3) and Aristaless-like homeobox 4 (ALX4) have been identified as age-related genes that play a significant role in BC progression [141]. Thus, DYNLT3 was found to be highly overexpressed in both BC tissues and BC cell lines, in association with N-cadherin and vimentin (VIM) overexpression associated with E-cadherin downregulation, while DYNLT3 silencing suppressed cell growth, migration and invasion via the epithelial-mesenchymal transition (EMT) and induced cell apoptosis in MDA-MB-231 and MCF7 BC cells [142]. Interestingly, Aktary et al (2021) showed that the level of DYNLT3 is dependent on β-catenin activity, revealing a function of the canonical Wnt/β-catenin signaling pathway during melanocyte and skin pigmentation [143].…”
Section: Age-related Disparities In Breast Cancermentioning
confidence: 99%